A prospective review of alccofine as supplementary cementitious material. (2021) - Srinath, B.L.N. Sai; Patnaikuni, Chandan Kumar; Balaji, K.V.G.D.; Kumar, B. Santhosh; Manjunatha, M.
Abstract: The purpose of this review article is to effective utilization of alccofine as a supplementary cementitious material (SCM) in concrete. Concrete is the most extensively used man-made construction materials in the ecosphere. Cement is the binder material for producing the concrete. During the clinkering process in cement industry, large amount of CO2 is produced as a byproduct and emits into the atmosphere. This CO2 dominates the major share of total greenhouse gases (GHG) released in to the atmosphere. Hence to reduce GHG emission, research activities have been transforming from conventional materials to other supplementary materials. To support the recent research evident researchers are using, fly ash, GGBS, Rice husk ash (RHA), silica fume, Phosphogypsum, Metakaolin, etc. are widely used as a SCM in concrete due to pozzolanic reactivity. One among the SCM, alccofine (1203), is a recent trend microfine material that can be used in concrete as a partial replacement material for cement. This review paper presents a summary of the published literature by several researchers who have intended to highlight the importance of alccofine as a SCM in the various fields of the concrete industry. In this review article authors exhibiting a detailed review on utilization of alccofine as a SCM to improve the fresh, mechanical & durability properties of concrete. Each byproduct has a varying mineral content. Alternatively, there is huge problem for the disposal of the byproducts. They appraised the alccofine, when partly replaced with cement, showed a remarkable improvement in both mechanical as well as durability properties at all ages. But the micro structure and fire resistance properties were not yet approached by the current research, hence this gap is addressed as a future course of research.